Student-to-Teacher Victimization and Its Negative Impact on Teaching Approaches: Applying Propensity Score Matching - Choi, Jaeyong (Journal of interpersonal violence, 2024)
The negative impact of student-to-teacher victimization on teachers’ perceptions of the work environment and their well-being is supported by growing empirical literature. For instance, violence in the classroom can have a negative impact on teachers themselves and hinder teachers from playing crucial roles in students’ classroom experiences, resulting in adverse effects on student performance. However, the research field is limited in understanding the adverse effects on teachers’ perceptions more directly related to student learning, such as teacher neglect. To fill the gap in the literature, the current study analyzes data from a nationwide sample of 1,054 middle and high school teachers in South Korea where teachers are generally treated with high regard and social status, often exerting a strong influence and authority over students in both an educational and parental way. Specifically, we conduct propensity score matching to investigate potential influences that student-to-teacher victimization can have on the following three outcome variables: teacher neglect, commitment, and pride. Results of mean comparisons after accounting for other confounding factors show that when compared with nonvictims, victims of student-to-teacher victimization are more likely to neglect their students; these victims also tend to exhibit less pride as teachers. Yet, the results also showed no significant statistical difference in teacher commitment. The current findings highlight the importance of developing programs to prevent and intervene in students’ aggressive behaviors toward teachers. Particularly, administrators are recommended to consider providing training for teachers, specific to understanding student-to-teacher victimization in order to promote a more positive school environment and better student-to-teacher relationships in classrooms, including improving teachers’ job performance.